China's soil and groundwater management challenges: Lessons from the UK's experience and opportunities for China - Coulon, Frederic; Jones, Kevin C.; Li, Hong; Hu, Qing; Gao, Jingyang; Li, Fasheng; Chen, Mengfang; Zhu, Yong-Guan; Liu, Rongxia; Liu, Ming; Canning, Kate; Harries, Nicola; et al. (Elsevier, 2016)
There are a number of specific opportunities for UK and China to work together on contaminated land management issues as China lacks comprehensive and systematic planning for sustainable risk based land management, encompassing both contaminated soil and groundwater and recycling and reuse of soil. It also lacks comprehensive risk assessment systems, structures to support risk management decision making, processes for verification of remediation outcome, systems for record keeping and preservation and integration of contamination issues into land use planning, along with procedures for ensuring effective health and safety considerations during remediation projects, and effective evaluation of costs versus benefits and overall sustainability. A consequence of the absence of these overarching frameworks has been that remediation takes place on an ad hoc basis. At a specific site management level, China lacks capabilities in site investigation and consequent risk assessment systems, in particular related to conceptual modelling and risk evaluation. There is also a lack of shared experience of practical deployment of remediation technologies in China, analogous to the situation before the establishment of the independent, non-profit organisation CL:AIRE (Contaminated Land: Applications In Real Environments) in 1999 in the UK. Many local technology developments are at lab-scale or pilot-scale stage without being widely put into use. Therefore, a shared endeavour is needed to promote the development of technically and scientifically sound land management as well as soil and human health protection to improve the sustainability of the rapid urbanisation in China.
Keywords: Contaminated land management; Rapid urbanisation; Risk assessment; China; UK